PEMENUHAN KEBUTUHAN PENGHARGAAN PADA MASA REMAJA (Studi terhadap Peserta Didik di Kelas X SMA Negeri 1 Kinali Pasaman Barat) - Wati, Elmi - (Bimbingan dan Konseling, 2014)
Student Senior High School is in a period of adolescent growth which have variousrequirement and still found by requirement of student teen-age which not yet fufilled speciallyrequirement of appreciation.Target of research for the deskription of accomplishment ofrequirement of appreciation at student teen-age in class of X SMA Negeri 1 Kinali Pasaman Barat.This research represent quantitative descriptive research. Population in this research is student ofclass of X SMA Negeri 1 Kinali Pasaman Barat school year 2013 / 2014 amounting to 366 student.Technique intake of sampel that is simple random sampling, taken as sampel in research amount to78 responder. Research instrument is enquette, for the analysis of data used by percentagetechnique. Result of research lay open that accomplishment of requirement of appreciation atstudent teen-age in class of X SMA Negeri 1 Kinali Pasaman Barat of appreciation by teacher ingeneral less fufilled.